Motivasi menjadi wirausaha di daerah Karawang - Al izzah, Hadrotul Khairun Nissa; Samoedra, Artarina D. A. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The presence of the role of entrepreneurs will have an impact on improving the state of the country's economy and the progress of the Indonesian economy. The Indonesian government must participate in providing support to generate public interest in entrepreneurship so that the problem of the lack of employment opportunities is resolved. The purpose of this study is to analyze four factors that influence the motivation to become an entrepreneur in Karawang, including need for achievement, locus of control, independence, and egoistic passion. The research approach used is descriptive qualitative and research using exploratory case study methods used to obtain information, problems and motivation to become entrepreneurs in Karawang. Data collection techniques are used for direct observation, interviews, and documentation. The results suggests that there are four factors for the emergence of entrepreneurial motivation owned by entrepreneurs in Karawang, as well as success in entrepreneurship because of the fulfillment of intrinsic needs. These factors can lead to someone having entrepreneurial motivation Need for achievement, Locus of control, Independence, egoistic passion. Their motivation to become entrepreneurs is driven by self-motivation or intrinsic motivation, where the drive aims to achieve the goals they want and their self-satisfaction, as well as success in entrepreneurship because of the fulfillment of intrinsic needs.